Bioactivity of Acanthus mollis – Contribution of benzoxazinoids and phenylpropanoids. (5th December 2018) - Matos, P.; Figueirinha, A.; Paranhos, A.; Nunes, F.; Cruz, P.; Geraldes, C.F.G.C.; Cruz, M.T.; Batista, M.T.
Abstract: Ethnopharmacological relevance: Acanthus mollis is a plant native to the Mediterranean region, traditionally used as diuretic, anti-inflammatory and soothing of the mucous membranes of the digestive and urinary tract and externally as healing of wounds and burns, also demonstrating analgesic and anti-inflammatory activities. However, studies focused on its phytochemical composition as well as scientific proof of Acanthus mollis efficacy are scarce. Aim of the study: The proposed work aims to perform a phytochemical characterization and evaluation of the therapeutic potential of Acanthus mollis, based on biological properties that support its traditional uses. Material and methods: In this study, an 96% ethanol extract from Acanthus mollis leaves was obtained and its phytochemical composition evaluated using High Performance Liquid Chromatography with Photodiode Array Detector coupled to Electrospray Ionization Mass Spectrometry (HPLC-PDA-ESI/MS n ). The chemical structure of the compound isolated was elucidated using 1 H and 13 C Nuclear Magnetic Resonance (NMR), 1 H-correlation spectroscopy ( 1 H–COSY), heteronuclear single quantum correlation (HSQC) and heteronuclear multiple-bond correlation (HMBC). The quantification of the constituents was performed using two external standards (2, 4-dihydroxy-1, 4-benzoxazin-3-one and verbascoside). The antioxidant activity was determined by the 2, 2-diphenyl-1-pycrylhydrazyl (DPPH) assay. Anti-inflammatory activity was determined measuring the inhibition of nitric oxide production by RAW 264.7 macrophages stimulated with the TLR4 agonist lipopolysaccharide (LPS) and through lipoxygenase (LOX) inhibition assay. The cytotoxicity was screened on two lines (RAW 264.7 and HaCaT) using the resazurin assay. Results: Compounds such as verbascoside and its derivatives, as well as benzoxazinoids were found as the main constituents. A percentage of 5.58% was verified for the 2, 4-dihydroxy-1, 4-benzoxazin-3-one (DIBOA) derivatives. DIBOA was the main compound of the extract. Significant concentrations were also found for phenylpropanoids, which constitute about 4.39% of the total compounds identified. This extract showed antioxidant capacity against DPPH (IC50 = 40.00 ± 1.59 μg/mL) and superoxide anion (IC50 = 29.42 ± 1.99 μg/mL). It also evidenced anti-inflammatory potential in RAW 264.7 macrophages, presenting capacity for nitric oxide reduction (IC50 = 28.01 μg/mL). Moreover, in vitro studies have shown that this extract was able to inhibit the lipoxygenase, with an IC50 of 104.39 ± 4.95 µg/mL. Importantly, all effective concentrations were devoid of cytotoxicity in keratinocytes, thus highlighting the safety of the extract for the treatment of skin inflammatory related diseases. Concerning macrophages it was also possible to disclose concentrations showing anti-inflammatory activity and without cytotoxicity (up to 30 µg/mL). The benzoxazinoid DIBOA demonstrated a considerable anti-inflammatory activity suggesting its important contribution to this activity. Conclusions: These results corroborate the anti-inflammatory properties traditionally attributed to this plant. Among the compounds identified in this study, benzoxazinoids exhibited a significant anti-inflammatory activity that was never previously described. Ethanol seems to be a good option for the extraction of these bioactive compounds, since relevant antioxidant/anti-radical and anti-inflammatory activities were found for this extract. Graphical abstract: